Reconstruction of Light Organ in Squid With The Histological Method of Electron Transmission Microscope - Delianis Pringgenies; Dafit Ariyanto (Masyarakat Moluska Indonesia, 2021)
The light organ is an electronic device that can emit light. However, there are light organs in animals that can produce light naturally. Loligo duvaucelii is a species whose biolumenesence comes from fluorescent bacteria that live in symbiosis in its ink sacs. This study aims to determine in detail the construction of the squid light organ using the transmission electron microscopy (TEM) method. The results showed that this type of squid has a pair of light organs attached to the dorso-lateral ink sac. The light organ is spherical, some are found on the surface and some are embedded on the wall of the ink sac. It consists of a lens that is located on the outer surface of the ink sac, and a sac of light organs (embedded on the wall of the ink sac) with channels connecting the pocket to the mantle cavity. The wall of the sac of the light organ consists of three layers, namely the innermost layer which is multi-fold with microvilli on the cell surface and between the folds of the sac populated with bacteria, the dense layer that acts as a reflector, and the pigment layer. Cilia are observed on the surface of the duct connecting the sac with the mantle cavity. This study concluded that the construction of the squid light organ has a convex-shaped lens structure and is muscular. In the pockets of light organs, a dense population of bacteria is found. The reflector consists of many layers, and the pigment layer contains many granules.